Картины социального мира: концепты общества и субъекта действия в социологической теории - Отрешко, Н. (Социология: теория, методы, маркетинг, 2009)
Patterns of the world may be defined as systems of ideas about reality. These systems are accepted in the culture of the certain socio-historic areal. Patterns of the world set the stage for world perception by human being as a subject of cognition and as an actor. Actor’s views are conditioned by such an interpretations of reality as self evident for actors. Thus this way of reality interpretation or Weltanschauung dominates in mass consciousness in certain socio-cultural space. Intellectual elite elaborates the interpretation of social reality addressed to all social groups. In the Middle Ages, Catholic Church held the monopoly of the universal version of reality interpretation which shaped the religious pattern of world. Starting from the Age of the Enlightenment, patterns of social reality have been shaped by philosophers or, later on, by theoretical sociologists in consequence of secularization process. These developments, as well as concepts of society and actor are treated by objectivist and subjectivist sociological theories in different ways. Such a divergence of opinion is conditioned both by philosophical and by political ideas of theorists.